At Home in the Heart of the Horseshoe : Life in the University of South Carolina President's House - Moore-Pastides, Patricia (Book collections on Project MUSE., 2017)
"Much has been written about the relationship between a president and his or her university. Many of the comments have become cliche. "It's not a job, it's an obsession," or "A president's life is a 24/7 commitment." One of the funniest quips defines a university president as someone who lives in a mansion but is always begging for money. How true! Far less has been written about the meaning and impact of actually living in the President's House, particularly a house located in the very heart of South Carolina's flagship university. Now, for the first time, Patricia has succeeded in rendering the house a home and has brought its former residents to life in this wonderfully approachable book. And even though I live in the house, I freely admit that, through Patricia's colorful recounting, I have become reacquainted with its rich history and understand our great good fortune to be its residents"--